66th International Open Readings Conference for students of Physics and Natural Sciences. Annual Abstract Book 2023 - Keršys, Martynas; Mickus, Šarūnas (Vilnius University Proceedings, 2023)
“Open Readings 2023” – is an international academic platform for students and young researchers from all over the world to present their ongoing research results and practices in the fields of physics and natural sciences.The 66th International Scientific Conference for Students of Physics and Natural Sciences gathers people to discuss, learn, exchange and share their scientific experience, meet key experts and enjoy an exciting programme. The conference includes lectures of well-known, leading and accomplished scientists and presentations of students’ research. “Open Readings 2023” gives an opportunity for BSc, MSc and PhD students, who are doing their scientific research, to present it to a larger audience, and get constructive criticism and helpful advice. This book gives an overview of all Open Readings 2023 conference presentations.